Importance of Business Intelligence Solution on Decision-Making Process of Companies - Serdar BIROĞUL; Hasan Berk GÜLTEKIN (International Journal of Applied Methods in Electronics and Computers, 2016)
Nowadays, many companies meet the needs of data from different data sources in different formats in order to in line with changing business needs. Data is managed and stored in different parts of the system. Business intelligence is the most effective solution that allows to see big picture by integrating all of the distributed data within a storage. Business intelligence has emerged as a natural result of the previous system designed to support the decision-making process. Over time, visual deficiencies discovered in decision support systems, difficulties of usages and mismatch between applications, is one of the major factors in the rise of business intelligence technology. Such solutions are up to date and integrated view of business performance it offers the greatest benefits to decision makers. By increasing centralization of data quality, control and scheduling capabilities have allowed us to take quick and right decisions in the evolving competitive environment. The concept of business intelligence is an important element of taking strategic decisions and implementation point in globalized world. This study has designed by Oracle business intelligence tool and results have been a key element of evaluation in decision making processes of the companies.